Inelastic electron tunneling across magnetically active interfaces in cuprate and manganite heterostructures modified by electromigration processes - Belogolovskii, M. A.; Revenko, Yu. F.; Gerasimenko, A. Yu.; Svistunov, V. M.; Hatta, E.; Plitnik, G.; Shaternik, V. E.; Rudenko, E. M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
We report a study of the electron tunneling transport in point-contact junctions formed by a sharp Ag tip and two different highly correlated oxides, namely, a magnetoresistive manganite La0.66Ca0.34MnO3 and a superconducting cuprate LaBa2Cu3O7-x. Strong chemical modifications of the oxide surface (supposedly, oxygen ion displacements) caused by applying high voltages to the junctions have been observed. This effect is believed to be responsible for an enormous growth of inelastic tunneling processes across a transition region that reveals itself in an overall "V"-shaped conductance background, with a strong temperature impact. The mechanism of the inelastic scattering is ascribed to charge transmission across magneticallyactive interfaces between two electrodes forming the junction. To support the latterstatement, we have fabricated planar junctions between Cr and Ag films with an antiferromagnetic chromium oxide Cr2O3 as a potential barrier and at high-bias voltages have found an identical conductance trend with a similar temperature effect.